Estimasi usia prajurit TNI AL berdasarkan Tooth Coronal Index pada digital radiograf panoramik - Reni Indah Yolanti; Suhardjo Sitam; Ganesha Wandawa; Farina Pramanik (Ikatan Radiologi Kedokteran Gigi Indonesia, 2020)
Objectives: The purpose was to determine the estimated chronological age difference between Indonesian Navy soldiers (TNI-AL) and dental age based on the Tooth Coronal Index on panoramic digital radiographs, which are used as antemortem data for the purposes of identifying Indonesian Navy soldiers if they have an accident while on duty or on the battlefield where only tooth remains. Material and Methods: The method used was a cross-sectional observational survey with the sampling technique using purposive sampling. This study used 86 digital panoramic radiographs of Indonesian Navy soldiers who were assigned abroad from 2015-2017 at the Dental Radiology Installation of Ladokgi TNI AL R.E. Martadinata. The teeth measured were mandibular first molars with the Tooth Coronal Index (TCI) method, which is a method of estimating age based on secondary dentin deposition and tooth pulp size on dental radiographs. Results: The results of the chronological age difference with the dental age of Indonesian Navy soldiers using the Tooth Coronal Index (TCI) method on a panoramic digital radiograph performed on mandibular first molars were an average of 6.3 years. Conclusion: The dental age of Navy soldier is higher than chronological age.